2017
DOI: 10.5530/ijper.51.3s.29
|View full text |Cite
|
Sign up to set email alerts
|

Harvest Number and Growing Season Effects on Quality and Health Related Compounds in Parsley

Abstract: Background and Purpose: Parsley is mostly grown outdoors and harvested seasonally. Farmers in many parsley producing countries, especially in the temperate region such as Turkey usually prefer spring sowings (summer growing season-SGS) and fall sowings (winter growing season-WGS) for open field production. Parsley can be usually harvested 4-8 times in temperate climates, if some special precautions are taken it may be 10-15 times. In arid, hot and cold climate regions, 2-4 harvests can be obtained. Material an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Overall, shoot phytochemical compounds content (except shoot AsA) decreased in the second harvest. This was also reported in parsley [ 60 ] and basil [ 61 ]. In Cichorium spinosum , the decrease in phytochemical accumulation only occurred after the second harvest [ 40 ].…”
Section: Resultssupporting
confidence: 78%
“…Overall, shoot phytochemical compounds content (except shoot AsA) decreased in the second harvest. This was also reported in parsley [ 60 ] and basil [ 61 ]. In Cichorium spinosum , the decrease in phytochemical accumulation only occurred after the second harvest [ 40 ].…”
Section: Resultssupporting
confidence: 78%
“…Therefore, the higher numbers of compounds detected in other reports may be related to the implemented extraction methods as well as to other factors already reported in the literature (genotype, growing conditions, growth substrate, harvesting time, cultivation practices etc. ), which can alter the chemical composition and the profile of secondary metabolites in plants [7,12,19,20,[33][34][35][36]. Moreover, Grúz et al [37], who detected hydroxycinnamic acids such as coumaric, ferulic and sinapic acids in parsley leaves, suggested that these compounds are prone to oxidation and degradation, which may affect their identification in plant samples.…”
Section: Phenolic Compound Compositionmentioning
confidence: 99%
“…In this line, the unstable nature of abiotic factors throughout plant vegetation adjusts the specificities of metabolic courses and the chemical profile and composition of biologically active constituents. The biosynthetic processes may be influenced by numerous factors such as the meteorological conditions, the harvesting time, the genotype, the irrigation regime and the planting density, among others [19][20][21][22]. It was also observed that parsley in the autumn harvest accumulates more polyphenols and pigment complexes (β-carotene) than plants grown in spring, which could be associated with the variation of the environmental effects.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of parsley is the Mediterranean region and the Western Asia, but today it is cultivated throughout the world. For centuries it is used as an aromatic vegetable, to garnish and to give flavour and odour to dishes and salads [2,3]. In addition, it is commonly used in the food industry, the perfume manufacturing, and for medicinal purposes in the traditional and folk medicine [3,4].…”
Section: Introductionmentioning
confidence: 99%